Employing a decision support system (DSS) with the checklist method to improve small retailers’ locational decisions - Syed Nasirin Syed Zainol Abidin; Carolyn Salimun; Dinna N. Mohd Nizam; Esmadi Abu Abu Seman; Hadzariah Ismail; Iza A. Ahmad Bahar; Zaidatol H. Abdullah Sani (Association for Computing Machinery, 2025)
Choosing the right location is vital for small retailers, as it significantly influences visibility, customer access, and long-term profitability. Traditional location selection methods rely on limited data, which may lead to less-than-ideal outcomes. This paper examines how integrating the Checklist Method (CM) with a web-based Decision Support System (DSS) may improve locational decision making for small retailers in Malaysia. Many small retailers still need help making data-driven decisions despite online tools and technology availability. A DSS application enables retailers to evaluate potential locations against a comprehensive predefined criterion, resulting in more objective and strategic choices. By combining the CM with a DSS, small retailers gain a practical framework that empowers them to make informed and strategic location choices. The findings highlight the significant advantages of this integrated approach, demonstrating its potential to convert the retail location selection process across diverse market contexts, even in an era where online technology is readily accessible.